Authentic Leadership and Whistleblowing: Mediating Roles of Psychological Safety and Personal Identification - Liu, Sheng-min (Journal of business ethics, 2015)
The issues of organizational wrongdoing damage organizational performance and limit the development of organizations. Although organizational members may know the wrongdoing and have the opportunity to blow the whistle, they would keep silent because of the interpersonal risks. However, leaders can play an important role in shaping employee whistleblowing. This study focuses on discovering the mechanisms of how authentic leaders influence employee whistleblowing with a sample from China. Results demonstrate that authentic leadership is positively related to internal whistleblowing. Team psychological safety partly mediates the relationship between authentic leadership and internal whistleblowing. Personal identification partly mediates the relationship between authentic leadership and internal whistleblowing. The study contributes to the extant theory by filling the gap between leadership and whistleblowing.